Transcription regulation of African swine fever virus: dual role of M1249L - Dongming Zhao; Nan Wang; Xiaoying Feng; Zhenjiang Zhang; Kongen Xu; Tao Zheng; Yunge Yang; Xuemei Li; Xianjin Ou; Rui Zhao; Zihe Rao; Zhigao Bu; et al. (Nature Communications)
Abstract African swine fever virus (ASFV), which poses significant risks to the global economy, encodes a unique host-independent transcription system. This system comprises an eight-subunit RNA polymerase (vRNAP), temporally expressed transcription factors and transcript associated proteins, facilitating cross-species transmission via intermediate host. The protein composition of the virion and the presence of transcription factors in virus genome suggest existence of distinct transcription systems during viral infection. However, the precise mechanisms of transcription regulation remain elusive. Through analyses of dynamic transcriptome, vRNAP-associated components and cell-based assay, the critical role of M1249L in viral transcription regulation has been highlighted. Atomic-resolution structures of vRNAP-M1249L supercomplex, exhibiting a variety of conformations, have uncovered the dual functions of M1249L. During early transcription, M1249L could serve as multiple temporary transcription factors with C-terminal domain acting as a switcher for activation/inactivation, while during late transcription it aids in the packaging of the transcription machinery. The structural and functional characteristics of M1249L underscore its vital roles in ASFV transcription, packaging, and capsid assembly, presenting novel opportunities for therapeutic intervention.